The Development Process of Managing Virtual Training for Teachers - Rafiza, A.R.; Yusop, F.D.; Perumal, Y.; Chukumaran, S.R.
This paper explores the developmental process of managing virtual training for 120 teachers from three different schools. Training sessions were administered in two phases: authentic environment and face-to-face virtual environment. Observation and content analysis were the two techniques employed in collecting the data. The outcome of the research was production of a system for managing virtual training for teachers.